2017
DOI: 10.1159/000479559
|View full text |Cite
|
Sign up to set email alerts
|

Malpractice Litigation in Ocular Oncology

Abstract: Aims: The aim of this study was to report and analyze the causes and outcomes of ocular oncology malpractice litigation. Methods: The WestLaw® database was reviewed for all litigation related to ophthalmology in the United States from 1930 to 2014. All ocular oncology cases were included in this analysis and compared to other ophthalmic subspecialties. Results: Sixteen ocular oncology malpractice cases were included in this study. Overall, 56.3% of the cases were resolved in favor of the defendant. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…This review of 44 medical malpractice cases in ophthalmic trauma draws attention to commonly litigated clinical scenarios for the purpose of improving clinical management through dedicated analysis of risk. To our knowledge, this is the only review specifically analyzing malpractice cases in ophthalmic trauma, which complements existing publications on litigation in ophthalmology, [7][8][9][10] while drawing special attention to many ophthalmic emergencies. The cases in this series represent some of the most common ophthalmic trauma scenarios, many of which often have poor outcomes due to the severe nature of these injuries, highlighting the importance of understanding the appropriate management of these conditions as well as the importance of documentation and expectation management.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This review of 44 medical malpractice cases in ophthalmic trauma draws attention to commonly litigated clinical scenarios for the purpose of improving clinical management through dedicated analysis of risk. To our knowledge, this is the only review specifically analyzing malpractice cases in ophthalmic trauma, which complements existing publications on litigation in ophthalmology, [7][8][9][10] while drawing special attention to many ophthalmic emergencies. The cases in this series represent some of the most common ophthalmic trauma scenarios, many of which often have poor outcomes due to the severe nature of these injuries, highlighting the importance of understanding the appropriate management of these conditions as well as the importance of documentation and expectation management.…”
Section: Discussionmentioning
confidence: 90%
“…Query of the Westlaw ® database yielded 1261 appellate cases and 1294 jury verdicts/settlements; 1063 cases met inclusion criteria. [7][8][9][10] Forty-four ophthalmic trauma malpractice cases were identified from the database, representing 4.1% of total cases (Supplementary Table 1). The 44 ophthalmic trauma cases occurred between 1967 and 2013 ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These trends are consistent with the limited literature on the subject and may be secondary to improved medical care over time, increased requirement of burden of proof for the plaintiffs, and/or lead time bias. 5,20 The most common reason for a decision in favor of the defendant was that no deliberate indifference was undertaken by the prison staff/physicians (46%). This indicated that the staff/physicians acted accordingly and did not intentionally mismanage the prisoner's medical care; however, this was not a comment on the quality of provided care.…”
Section: Collateral Estoppelmentioning
confidence: 99%